Effectiveness Of Building Openings In Achieving Thermal Comfort In Semi-Outdoor Spaces: A Case Study Of Taman Dayu Hotel, Indonesia - Marsa Niswa Fauzyyah; Rizka Tiara Maharani (International Journal of Health Engineering and Technology, 2026)
Thermal comfort in tropical hospitality buildings presents significant challenges due to persistently high temperatures and humidity levels. Semi-outdoor spaces, frequently integrated into hotel designs, rely primarily on natural ventilation and spatial openness to regulate environmental conditions. However, the effectiveness of building openings in supporting passive thermal performance varies depending on configuration, orientation, and airflow continuity. This study investigates the relationship between building opening configurations and measured thermal conditions across different spatial typologies at Taman Dayu Hotel, Indonesia. A field-based mixed-method approach was employed, combining quantitative environmental measurements with qualitative architectural analysis. Air temperature and relative humidity were recorded in indoor, semi-outdoor, and outdoor spaces, while opening size, distribution, cross-ventilation potential, and shading conditions were documented through direct observation. Comparative analysis was conducted to evaluate how spatial permeability and airflow pathways influence thermal performance. The findings indicate that semi-outdoor spaces with opposing openings and unobstructed airflow paths exhibit more stable and moderate thermal conditions compared to spaces with single-sided openings. Cross-ventilated corridors and restaurant areas demonstrate improved passive performance, while fully open zones without adequate radiation control record higher temperatures despite large opening areas. The results emphasize that opening size alone does not ensure thermal moderation; rather, effective airflow continuity, spatial configuration, and integration of shading strategies are critical in achieving passive thermal performance. This study provides empirical evidence supporting the optimization of opening design strategies in tropical hospitality architecture to reduce reliance on mechanical cooling systems.